MASS CULTIVATION AND DETERMINATION OF BIOCHEMICAL COMPOSITION OF SPIRULINA PLATENSIS IN THREE DIFFERENT MEDIUM - MANIGANDAN M (International Journal of Pharma and Bio Sciences, 2014)
In this work, Spirulina platensis was cultivated using three different media viz., Synthetic medium (SM), Fertilizer medium(FM) and Seawater medium(SW) in which growth and proximal concentration of Protein, crude fat, total carbohydrate, total phenol, Chlorophyll content, carotenoid content and the crude phycocyanin content were examined for 5 days interval period upto 25 days of cultivation. Direct microscopic count (DMC), Optical density (OD) at 560 nm and the Dry biomass (DB) were examined from three different media used and it was found that maximum growth was obtained in Synthetic medium (DMC-95 cells/ml, OD-0.442 nm, DB-2.55 mg/l), followed by Fertilizer medium (DMC-89 cells/ml, OD-0.395 nm, DB-2.10 mg/l) and the least growth was obtained in Seawater medium (DMC-55 cells/ml, OD-0.251 nm, DB-0.91 mg/l).